Effect of Screen Media Technologies on Physical and Psychological Well Being in Middle Aged Adults - Singh, Priya; Bhardwaj, Prabhas; Sharma, Sushil Kumar; Agrawal, Anil Kumar (IGI Global, 2023)
Screen media technologies (SMTs) has become an essential part of human life and almost everybody, irrespective of their age group, uses one or the other screen media technologies. Increased dependency on SMTs is raising concerns over their ill effect on the psychological health of its users. The present work aims to study the impact of social media usage and laptop/computer on psychological and physical health. This is a cross-sectional study of the middle management employees of a major Indian telecom organization. The analyses were carried out using structural equation modelling (SEM) approach. Results suggested that neck pain is directly related to cognitive stress, somatic stress, and laptop/computer usage. Cognitive stress was indirectly related to Instagram and WhatsApp use. Behavioural stress had no direct or indirect relationship with social media or laptop/computer use. Using a laptop/computer is found to be the most critical factor contributing to neck pain in Indian middle-aged adults working in an office environment.
This paper published with affiliation IIT (BHU), Varanasi in Open Access Mode.
Keywords: Behavioural Stress; Cognitive Stress; Middle Aged Adults; Neck Pain; Physical Well Being; Psychological Well Being; Somatic Stress; Structural Equation Modelling